Kesadaran Hukum tentang Perkawinan Tungku Cu (Perkawinan Sedarah) di Kampung Timung, Desa Golo Cador Kecamatan Wae Ri’i, Kabupaten Manggarai - Maria Febrianti Jesika Tanur; Sukardan Aloysius; Orpa Juliana Nubatonis (Jurnal Hukum dan Sosial Politik, 2024)
Furnace cu marriage is a marriage carried out between the daughter of a brother and the son of a biological sister. The marriage of the furnace cu has been carried out since ancient times so that it is carried out from generation to generation by the people of Timung Village. This marriage is an incestuous marriage prohibited in Law Number 1 of 1974 concerning Marriage in Article 8b. At the time the marriage law came into force in 1974, there were still those who carried out cu furnace marriages (inbreeding). The formulation of the problem from the research is: How is the legal awareness of the people of Kampung Timung, regarding furnace cu marriage (inbreeding) which is prohibited in Law Number 1 of 1974 concerning Marriage? And How is the existence of the furnace cu marriage in Timung Village at this time? The purpose of this study is to determine the legal awareness of the people of Timung Village regarding furnace cu marriage (inbreeding) which is prohibited in Law Number 1 of 1974. The second purpose is to find out the existence or existence of the cu furnace marriage in Timung Village at this time. The type of research used in this study is a type of empirical legal research. The data sources used in this study are primary data and secondary data. Data processing and analysis techniques, namely editing, coding, data systematization, then the data obtained both primary and secondary data will be processed and analyzed by researchers based on problem formulations. Based on the results of research that researchers have conducted, legal awareness of the Timung Village Community is still low because the Timung Village Community does not know and understand that cu furnace marriage (incestuous marriage) is prohibited in the Marriage Law, so that after the Marriage Law has come into effect in 1974 the Timung Village community still practices cu furnace marriage until 2005. The legal awareness of the Timung Village Community after the Marriage Law came into effect in 1974 against the ban on marriage was caused by several factors such as, customary factors, low level of education, compulsion due to arranged marriages by parents, lack of legal counseling from the government regarding the prohibition of marriage contained in Law Number 1 of 1974 concerning Marriage. The existence of furnace cu marriages at this time, is rarely found and has begun to fade, influenced by several factors such as bans from the church, fear that offspring will be born defective, the influence of social media.